Indonesia Economic Quarterly, March 2017 : Staying the Course - World Bank (World Bank, Washington, DC, 2018)
With a robust rate of economic growth, low current account deficit, a conservative fiscal deficit and inflation at a record low, the fundamentals of the Indonesian economy continue to be strong. Despite global policy uncertainty, economic growth strengthened in 2016 on the back of higher private consumption growth. The economic outlook remains positive, supported by a projected pick-up in the global economy and recovering commodity prices, carrying both investment and exports.Major shifts in trade policies among advanced economies, unexpected changes in U.S. monetary policy, political uncertainty in Europe, a protracted period of elevated domestic inflation, and weak fiscal revenues pose significant downside risks. Real GDP growth in Q4 2016 eased to 4.9 percent yoy from 5.0 percent in Q3, as government expenditure continued contracting and import growth rebounded. The 4.0 percent decline in government expenditure was the largest since Q1 2010, due in part to base effects of strong expenditure growth in Q4 2015. Meanwhile investment growth rose and export growth turned positive after eight quarters of contraction, in line with stronger commodity prices.